Pengembangan Modul Ipa Berbasis Research Based Learning Pada Keterampilan 4C Tema Hubungan Antar Makhluk Hidup dan Lingkungannya Siswa Sekolah Dasar - Rumahorbo, Rani Hotmaida; Prananda, Gingga; Estuhono, Estuhono (Innovative: Journal Of Social Science Research, 2021)
So far, very low 4C education for students has not been a major concern in elementary schools and has not been applied to every subject in elementary schools, therefore this study aims to develop a Research Based Learning (RBL) science module. So the purpose of this study is to improve the way of learning in elementary schools, especially in science subjects for fifth grade students. The 4-D development consists of the stages of defining, designing, developing, and distributing. The defining stage includes curriculum analysis, student characteristics analysis, and material analysis. In the development stage, validity test, practicality test and effectiveness test were carried out. The results of the learning device validation assessment carried out by three experts had a content validation score of 84.37%, a language validation score of 87.5%, and a construct validation score of 75%, the average validation score was 82.29% with a very valid category. seen from the components of the learning device. The results of the practicality assessment of learning devices carried out by classroom teachers had a score of 87.49% with a very valid category. The assessment of this effectiveness test resulted in 75% with the effective category, this study resulted in a science module with very valid and effective criteria.